Proposing Robust IRWs Technique to Estimate Segmented Regression Model for the Bed load Transport of Tigris River with Change Point of Water Discharge Amount at Baghdad City - عباس, محمد احمد; علي, عمر عبد المحسن (Journal of Economics and Administrative Sciences, 2020)
Segmented regression consists of several sections separated by different points of membership, showing the heterogeneity arising from the process of separating the segments within the research sample. This research is concerned with estimating the location of the change point between segments and estimating model parameters, and proposing a robust estimation method and compare it with some other methods that used in the segmented regression. One of the traditional methods (Muggeo method) has been used to find the maximum likelihood estimator in an iterative approach for the model and the change point as well. Moreover, a robust estimation method (IRW method) has used which depends on the use of the robust M-estimator technique in segmentation ideas and using the Tukey weight function. The research’s contribution lies in the suggestion to use the S-estimator technique and using the Tukey weight function, to obtain a robust method against cases of violation of the normal distribution condition for random errors or the effect of outliers, and this method will be called IRWs. The mentioned methods have been applied to a real data set related to the bed-load of Tigris River/ Baghdad city as a response variable and the amount of water discharge as an explanatory variable. The results of the comparison showed the superiority of the proposed method.